Clinicopathological Description of a Chronic Lymphocytic Leukemia in a Dog - Boni, Raffi Maria Clara [UNESP]; Magalhães, Barbosa Giovanna Valverde [UNESP]; Capais, Rodrigues Alana Carolina; Canevese, Rahal Sheila [UNESP]; P., Kastelic John; Dercore, Benevenuto Luíz Guilherme [UNESP]; Simões, Braga Iolanda [UNESP]; Poloni, Batista Beatriz [UNESP]; Da Silva, Brasileiro Felipe César [UNESP]; de, Moura Fernanda Barthelson Carvalho [UNESP]; Guimarães, Okamoto Priscylla Tatiana Chalfun [UNESP]; Kiomi, Takahira Regina [UNESP]; et al. (Scientific Research Publishing, 2024)
Hematopoietic tumors are associated with diagnostic and therapeutic challenges and a poor prognosis. Furthermore, their pathophysiology in dogs is not well understood. Chronic lymphocytic leukemia has been rarely reported in golden retrievers, perhaps due to difficulties in diagnosis and care. An 8-year-old spayed female golden retriever was referred to our hospital with a 2-month history of fatigue, weakness, and selective appetite. The dog was diagnosed with chronic lymphocytic leukemia based on blood smear evaluation. Despite treatment, the dog deteriorated and the owners opted for euthanasia. Histopathological examination revealed atypical lymphocytes in the spleen, extramedullary hematopoiesis in the spleen and liver, bone marrow depletion, moderate neutrophilic myocarditis, and acute renal tubular necrosis. In an immunohistochemical panel, cells in the spleen and bone marrow were positive for anti-CD20, anti-CD45, anti-CD3, anti-IBA-1, anti-Ki67, anti-MUM-1, and anti-PAX-5. In conclusion, the leukemia diagnosis was confirmed through reactive histiocytosis, marked extramedullary hematopoiesis, and other clinical and laboratory findings. Herein, we report a case of chronic lymphocytic leukemia in a female dog with clinical, laboratory, and necroscopy findings.